The macrophage activation product sCD163 is associated with a less favourable metabolic profile in prepubertal children. Issue 6 (4th February 2016) - Carreras‐Badosa, G.; Prats‐Puig, A.; Diaz‐Roldan, F.; Platero‐Gutierrez, E.; Osiniri, I.; Riera‐Perez, E.; de Zegher, F.; Ibañez, L.; Bassols, J.; López‐Bermejo, A.
Summary: Objective: Macrophages are known to be involved in low‐grade inflammatory processes such as obesity. soluble cluster of differentiation 163 (sCD163) is shed from the cell surface as specific macrophage activation marker. In prepubertal children, we studied if circulating sCD163 is associated with metabolic and cardiovascular risk markers. Methods: A population of 236 school‐aged Caucasian children (111 girls and 125 boys) aged 8 ± 1 year [81 normal weight (body mass index [BMI]‐SDS < 1); 74 overweight (1 ≤ BMI‐standard deviation score [SDS] < 2) and 81 with obesity (BMI‐SDS ≥ 2)] were studied. BMI, waist circumference, fat mass and visceral fat were measured. Fasting serum sCD163, homeostatic model assessment of insulin resistance, high sensitivity C‐reactive protein, gamma‐glutamyl transpeptidase and lipids were quantified. Results: Circulating sCD163 concentrations were higher in children with obesity ( p < 0.0001). Associations were observed between circulating sCD163 and a less favourable metabolic profile as judged by higher waist circumference, fat mass, visceral fat, epicardial fat, homeostatic model assessment of insulin resistance, high sensitivity C‐reactive protein, gamma‐glutamyl transpeptidase and triglycerides (all between r = 0.173 and r = 0.363; p < 0.05 to p < 0.0001) and lower high‐density lipoprotein‐cholesterol ( r = −0.285, p < 0.0001). In multiple regression analyses, circulating sCD163 was independently associated with HOMA‐IR ( β = 0.162, p = 0.016; model R 2 = 0.179) and high density lipoprotein‐cholesterol/triglycerides ratio ( β = −0.167, p = 0.012; model R 2 = 0.209). Conclusions: Childhood obesity may increase the risk of developing metabolic diseases later in life through chronic macrophage activation having deleterious effects on metabolism.